Les avantages comparatifs du Luxembourg pour les investissements de la famille de Bertier des années 1830 aux années 1920 - Einrick, Stéphane (Hémecht. Zeitschrift für Luxemburger Geschichte = Revue d’histoire luxembourgeoise, 2025)
Abstract: „The Grand-Duchy Luxembourg has always attracted foreign investors, first Belgian and then German. The archives of the château de Lagrange, in Manom (Moselle, France), provide information on the Bertier family, a wealthy lineage of the French nobility, established near Luxembourg in the early 19th century. Their investments in the Luxembourgish economy grew, eventually constituting the majority of the family’s fortune in the 1920s. The Bertiers first gained a foothold there through geographical proximity, investing in agricultural land and then in securities related to the steel industry. Their assets remained located in Dudelange, but grew over time, integrating the Bertiers into the country's major economic and political networks. Following the First World War, marked comparative advantages emerged compared to France, particularly in terms of taxation. The Bertiers took profit from their long experience in Luxembourg to invest their fortune and income there, making it a safe haven for the family assets. The example of the Bertier family cannot be generalized to all French investors in Luxembourg, but in following their traces this article illustrates a series of factors that made the country attractive, as well as the mechanisms employed to invest one's wealth there.“
Keywords: Adel; Agrarmarkt; Eisen- und Stahlindustrie; Steuerwettbewerb; Unternehmen; Wirtschaftsbeziehungen

Une noblesse sur la frontière. La noblesse protestante picarde et le prince de Condé (1560–1570) - Joblin, Alain (Noblesses transrégionales. Les Croÿ et les frontières pendant les guerres de religion (France, Lorraine et Pays-Bas, XVIe–XVIIe siècle), 2021)
Keywords: Adel; Herrschaft; Konfession; Picardie; Protestantismus; Spanische Niederlande

Noblesses transrégionales. Grands propriétaires, chefs militaires et négociateurs de paix dans les sociétés de frontière pendant les guerres de religion (XVIe–XVIIe siècle) - Junot, Yves; Soen, Violet (Noblesses transrégionales. Les Croÿ et les frontières pendant les guerres de religion (France, Lorraine et Pays-Bas, XVIe–XVIIe siècle), 2021)
Keywords: Adel; Herrschaft; Konfession

Matérialiser sa noblesse sur la frontière des anciens Pays-Bas avec la France. Le patrimoine architectural de Charles de Croÿ, prince de Chimay et duc d’Aarschot (1560–1612) - Maekelberg, Sanne; Martens, Pieter (Noblesses transrégionales. Les Croÿ et les frontières pendant les guerres de religion (France, Lorraine et Pays-Bas, XVIe–XVIIe siècle), 2021)
Keywords: Adel; Architektur; Herrschaft

Noblesses transrégionales. Les Croÿ et les frontières pendant les guerres de religion (France, Lorraine et Pays-Bas, XVIe–XVIIe siècle) - Soen, Violet; Junot, Yves (Burgundica, 2021)
Keywords: Adel; Herrschaft; Konfession

How Local Politics Became a Matter of Transregional Concern. German and Dutch Pamphlets Calling Jülich Nobility to Assemble in Cologne, 1642–1651 - Romein, Christel Annemieke (Transregional territories. Crossing borders in the early modern Low Countries and beyond, 2020)
Keywords: Achtzigjähriger Krieg; Adel; Flugschrift; Herzogtum Jülich-Berg; Köln; Propaganda